P920Understanding arrhythmia mechanisms in patients with atrial septal defects. (18th June 2020) - O"neill, L; Sim, I; O"hare, D; Whitaker, J; Mukherjee, R; Roney, C; Razeghi, O; Niederer, S; Harith, A; Rosenthal, E; Jones, M; Wright, M; et al.
Abstract: Background: Atrial arrhythmias represent a major cause of morbidity and hospitalization in patients with atrial septal defects (ASD). Optimum treatment strategies are unknown since the mechanisms of arrhythmia are undefined in this cohort. Purpose: We investigated whether percutaneous ASD closure reduces atrial arrhythmias and subsequently examined the electrical and structural changes underpinning arrhythmogenesis in ASD patients. Methods: Meta-analysis was used to study the effect of closure on arrhythmias. Bi-atrial electrical dysfunction was assessed through invasive measurement of atrial voltage, refractory periods (ERP) over three drive trains (600, 450 and 300ms) and local conduction velocity (CV) with subsequent assessment of ERP and CV restitution. Structural remodelling was assessed through non-invasive quantification of fibrosis using cardiac MRI (CMR). Origin of ectopy was evaluated invasively using isoprenaline infusion and non-invasively using 24-hour Holter monitoring. Comparison was made to normal heart controls. Results Meta-analysis Meta-analysis of 25 studies found that percutaneous closure was associated with a weak reduction in atrial arrhythmias only in patients >40 years old (OR 0.777, 95% CI 0.616-0.979, P = 0.032). Electrical Remodelling On invasive assessment (21 ASDs; 21 controls), proportion of right atrial low voltage (<0.5mV) and scar (<0.05mV) was greater in ASD vs control patients (P = 0.02 and P = 0.039). In ASD patients, these parameters were greater in the right atrium vs the left atrium (P = 0.002 and P = 0.01). Right atrial ERP restitution slopes were steeper in ASD vs control patients (P = 0.016). Maximum right atrial CV and CV restitution slopes were greater in ASD vs control patients (P= 0.005 and P < 0.001 respectively) and CV decrement occurred at longer coupling intervals in the right atrium in ASD patients (P = 0.015). Structural Remodelling On CMR assessment (36 ASDs; 36 controls), bi-atrial fibrosis was greater in ASD vs control patients (P < 0.001). In ASD patients right atrial fibrosis was burden greater in patients with vs without atrial arrhythmias (P = 0.034). Arrhythmia Triggers On 24-hour Holter monitoring and during invasive isoprenaline infusion right and left atrial ectopy was equally prevalent in ASD vs control patients. Conclusion: This study highlights the importance of right atrial electrical dysfunction to the occurrence of arrhythmias in ASD patients with extensive right atrial remodelling (fibrosis, low voltage, steeper ERP and CV restitution) seen in ASD patients compared to normal heart controls. From the results of the meta-analysis it appears that percutaneous closure alone is insufficient to treat arrhythmias in ASD patients. Given the predominance of right atrial remodelling, right-sided ablation as an adjunct to conventional left-sided ablation should be investigated as a strategy to treat atrial arrhythmias in these patients.